From Code to Character: Cultivating Artificial Life through Human Values in Chiang’s The Lifecycle of Software Objects - Baral, Pabitra Raj (The Outlook: Journal of English Studies, 2026)
This article examines the role of human values in cultivating a meaningful artificial life as reflected in Ted Chiang’s The Lifecycle of Software Objects. It investigates how the digient life transfers from an autonomous code to an ethical character nurtured by human-centered values—care, affection, and responsibility. The existing study on this text highlights the posthuman identity and agency of artificial beings, yet pays little attention to how human values foster an ethical life for AI entities. Based on this research gap, this article argues that the digients in the text can survive and develop only through constant human nurturing, emotional bonding, and moral responsibility. It employs digital humanism, AI ethics, and care ethics as a combined framework and a qualitative textual analysis method to study how the digients’ moral growth relies on human commitment rather than technological coding. It finds that AI systems are not autonomous and independent; they survive and develop only through human emotional and ethical care. Human characters, such as Ana, are responsible and accountable for the digients’ moral capacities beyond the mere code systems. The article highlights the significance of human values even in AI environments. It will contribute to digital humanism, AI ethics, and broader discussions on human-technology relationships by foregrounding the centrality of human values in Human-AI relationships.